Developing measures of community competence in Barangay Talangan, Nagcarlan, Laguna - Abaca, Mark Joseph M.; Angelo, Donna Belle L.; Balajadia, Metel B.; Bulanadi, Maria Clarissa A.; Denilla, Eric Bryan M.; Evangelista, Anthony Lowell S.; Garcia, Joan A.; Leyva, Erwin William A.; Lumabi, Renelle C.; Manayan, Melvina Ceceilia R.; Padilla, Mary Angeli T.; Reyes, Elimae B.
Determining indicators of community competence is one of the least cultivated fields in nursing research and Community Health Nursing. The concept of community competence has been defined by Cottrell (1976) in eight dimensions: (1) self-other awareness and clarity of situational definition, (2) articulateness, (3) commitment, (4) machinery for facilitating participant interaction and decision making, (5) conflict containment and accommodation, (6) participation, (7) social support, (8) and management of relations with wider society. Though researchers have been conducted in these dimensions as that of Eng & Parker's (1994), indicators of community competence have not clearly been identified. Furthermore, the absence of an evaluation tool measuring community competence poses a challenge in health care research.